The importance of India in the economy of the Persian Gulf and the Sea of Oman during the Sassanid period - Chamankar, Mohammadjafar (Journal of Subcontinent Researches, 2024)
During the Sassanid period, commercial activities with the Indian subcontinent, especially its coastal areas, were developed through the Persian Gulf . By capturing the key areas, the connection between the Persian Gulf with the islands and ports of India was facilitated. The Sassanids built camps in the coastal areas of India and gradually Zoroastrian and Nestorian Christian immigrant merchants settled there. The sailors used to travel between the ports and islands of the Persian Gulf with India, loading and unloading goods. The purpose of this research is to examine the commercial relationship between the northern and southern shores of the Persian Gulf and the Sea of Oman with the Indian subcontinent in the Sassanid period.In the end, it is concluded that a set of positive factors, including the policy of port city in the Persian Gulf, the formation of a powerful commercial and military fleet, the knowledge of sea routes and the land and sea occupation of the shores of the Indian Ocean by the Sassanids, led to the expansion of the mutual prosperity of commercial centers. The Persian Gulf and the Indian subcontinent.
Keywords: Relations -- Oman -- Inde

Prehistoric Interactions between Oman and the Indus Civilization: Projecting the Past in the Present - Kenoyer, Jonathan Mark (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Relations -- Oman -- Inde

Prehistoric Interactions between Oman and the Indus Civilization: Projecting the Past in the Present - Kenoyer, Jonathan Mark (Sultan Qaboos and Modern Oman = 50 Years of the Omani Renaissance 1970-2020 Conference, 2020)
Keywords: Relations -- Oman -- Inde

India, Oman to cooperate in the field of archives (The Hindu, 2024)
India and Oman have decided to cooperate in the field of archives and a draft Executive Programme of Cooperation (EPC) has been agreed upon, the Union Culture Ministry said in a statement.
Keywords: Relations -- Oman -- Inde

Oman - Quamar, Md. Muddassir; Hameed, Sameena; Kumaraswamy, P. R. (Persian Gulf 2023: India’s Relations with the Region, 2023)
Oman is one of the most important countries in the Gulf region and has gradually been working to regain its political and strategic space after the power transition that brought Haitham bin Tariq al-Said as the new Sultan. Due to Covid-19 and other financial issues, the country has faced economic challenges and has been reaching out to rich GCC neighbours secure financial help and investment to overcome them. At the strategic level, Oman is one of the major regional countries that advocate accommodation of Iran in the regional politics and prefer political dialogue over confrontation to discuss and resolve difference with it and Arab Gulf states. India and Oman share a multidimensional and robust relationship encompassing trade, commerce, defence, security, political and diplomatic ties. Oman continues to attract greater Indian attentions mainly because of its strategic location and the potentials in strengthening economic and defence partnerships.
Keywords: Relations -- Oman -- Inde

الجالية الهندية و الإمامة الاباضية في عمان : دراسة في العلاقات المتبادلة بينهما في نماذج من التاريخ العماني بين عامي 1868 - 1920 - الفياض, مقدام عبد الحسن باقر (الخليج العربي, 2013)
حظيت الجالية الهندية في عُمان بمكانة متميزة لا تضاهى من بين مثيلاتها الجاليات الأجنبية الأخرى كالفارسية والأفريقية وغيرها، وذلك باستنادها الى العلاقات التاريخية والحضارية الوطيدة التي ربطت بين عمان وشبه القارة الهندية لعدة قرون مضت. أما الإمامة الاباضية فإنها بلا شك تعد معلماً أساسيا من معالم تاريخ عمان البعيد والقريب، وواحدة من القوى المهمة التي حركت الاحداث والتطورات وتحكمت بالأفراد والجماعات والعواطف والتوجهات في حياة معظم العمانيين. وتتجلى أهمية الموضوع في المحاولة لدراسة طبيعة العلاقات بين هاتين القوتين الهامتين اللتين تتربع إحداهما على قمة الهرم الديني أو الروحي والأخرى تحتل مكانة رفيعة في سلّم الاقتصاد والتجارة. \ وقد قُسّمت الدراسة الى عدد من المحاور، تناول الأول الجذور التاريخية لوجود الجالية الهندية في عمان وتطور دورها الاقتصادي، ودرس الثاني ماهية علاقتهم مع بريطانيا وتأثير حمايتها لهم على ترسيخ نفوذهم وتغير نظرة الناس إليهم. فيما ركز الثالث والرابع على مفهوم الإمامة وأهميتها التاريخ العماني، وحكمها بين عامي 1868-1871 وموقفها تجاه الجالية الهندية, وتخصص الخامس بكشف حقيقة الموقف بين الجالية الهندية وانتفاضة القبائل عام 1895، أما السادس فقد جاء ليلقي الضوء على تأثيرات ثورة الامامة 1913 على الجالية الهندية. \ واستعان الباحث بمصادر ومراجع متنوعة أتت في مقدمتها الكتب الوثائقية الأجنبية وأهمها ومجموعات سالدانا J.A. Saldanha وبيلي r.w. baily مجموعة عمان (الوثائق السرية). \ وعدداً من الرسائل و الاطاريح الجامعية العربية والانكليزية. واستفاد أيضاً من الكتابات المحلية وقائمة من البحوث والكتب المعربة والعربية والإنكليزية \
Keywords: Relations -- Oman -- Inde

العلاقات التجارية بين عمان والهند فى عهد الامامة الاباضية الثانية : (177-280ه/794-893م) - على, لطيفة صلاح عبد الهادي (جامعة الفيوم, 2016)
Keywords: Relations -- Oman -- Inde